2021
DOI: 10.3390/genes12111665
|View full text |Cite
|
Sign up to set email alerts
|

Histone Variant H2A.J Is Enriched in Luminal Epithelial Gland Cells

Abstract: H2A.J is a poorly studied mammalian-specific variant of histone H2A. We used immunohistochemistry to study its localization in various human and mouse tissues. H2A.J showed cell-type specific expression with a striking enrichment in luminal epithelial cells of multiple glands including those of breast, prostate, pancreas, thyroid, stomach, and salivary glands. H2A.J was also highly expressed in many carcinoma cell lines and in particular, those derived from luminal breast and prostate cancer. H2A.J thus appear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…We showed the overexpression of ten immunomodulatory peptides in gene level of BC epithelial cells versus normal and validated these results in chromatin level. The elevated expression of these AMPs in BC is also reported previously (30, 34, 35, 39, 40, 43, 44, 57, 58). However, the therapetuic use of these peptide against BC by manipulationg their expression is yet to be explored.…”
Section: Discussionsupporting
confidence: 86%
“…We showed the overexpression of ten immunomodulatory peptides in gene level of BC epithelial cells versus normal and validated these results in chromatin level. The elevated expression of these AMPs in BC is also reported previously (30, 34, 35, 39, 40, 43, 44, 57, 58). However, the therapetuic use of these peptide against BC by manipulationg their expression is yet to be explored.…”
Section: Discussionsupporting
confidence: 86%
“…Previous studies noted organ-specific differences in H2A.J protein expression in normal tissues generally, with strong labeling of luminal epithelial cells, even without IR exposure [ 27 ]. Here, we used IFM to visualize H2A.J expression within different cell types in lung tissue of mice exposed to different doses of IR.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, the fucosylation and sialylation inhibitor pictilisib affected the DNA repair capacity of lung cancer cells . The histone H2AFJ (cluster e) is usually expressed in luminal epithelial cells, although its role is still poorly understood . However, it was recently found that high H2AFJ expression in CRC cells correlated with a significantly worse prognosis and acquired chemoradiation resistance .…”
Section: Discussionmentioning
confidence: 99%
“… 114 The histone H2AFJ (cluster e) is usually expressed in luminal epithelial cells, although its role is still poorly understood. 115 However, it was recently found that high H2AFJ expression in CRC cells correlated with a significantly worse prognosis and acquired chemoradiation resistance. 116 Interestingly, this group of proteins also revealed other specimens with an important role in the cellular response to radiotherapy, such as XRCC5 and XRCC6.…”
Section: Discussionmentioning
confidence: 99%